General Election Commission (KPU) of Makassar Efforts to Encourage Community Participation in the 2018 Regional Elections - Nur, Hasruddin; Adi Sumandiyar; Amir, Arfenti; Iskandar, Abdul Malik; Jalal; Kasim, Hasanudin (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
This research aims to examine and describe the efforts of the Makassar City KPU in encouraging community participation in the implementation of the 2018 regional elections. This type of research uses qualitative descriptive research by determining the number of informants consisting of 9 informants selected using purposive sampling technique. The data collection techniques used were observation, interviews and documentation. The data analysis technique used by researchers goes through three work stages, namely data reduction, data presentation and drawing conclusions. The research results show that the KPU's efforts to encourage public participation in the 2018 regional elections include: a) carrying out regional elections professionally without black campaigns and the practice of money politics by ensuring that every citizen has the same rights and opportunities to participate in the regional election process, b) increasing voter participation by providing healthy political education by increasing public knowledge so that they can participate optimally in the regional election process, c) Transparency in the implementation of regional elections by providing information that is easily accessible, involving the public in decision making, using information technology, enforcing clear rules and sanctions, and involving independent supervision from supervisory institutions and civil society.